An Efficient Method for Model Compression for Federated Learning Scenarios - Morais, Renan; Veiga, Rafael; Bastos, Lucas; Rosário, Denis; Cerqueira, Eduardo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2025: Anais do XLIII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2025)
Traditional Machine Learning (ML) relies on centralized systems, requiring large amounts of sensitive data. In contrast, edge processing minimizes data transmission by performing computations locally, improving efficiency. In this context, Federated Learning (FL) is a decentralized machine learning approach that allows clients to train models collaboratively while keeping their data private. However, FL faces challenges such as high communication costs due to the large number of model updates between clients and the central server. In this paper, we introduce an efficient method for model compression for FL scenarios called HUFE-FL, which applies quantization to transform model parameters into discrete values, reducing their size, followed by Huffman encoding. This further compresses the model by efficiently encoding frequent symbols with fewer bits. Our main results show that HUFE-FL achieves up to 77.48% reduction in data transmission compared to traditional FL methods, with minimal loss in accuracy.